Physical medicine and rehabilitaion secrets (Hanley & Belfus, 2002)
This completely updated top-seller in physical medicine and rehabilitation continues the tradition of the highly popular Secrets Series®. From anatomy and physiology of the nervous and musculoskeletal system to medical complications in rehabilitation to work and rehabilitation-this book presents all the key elements you need for clinical use, rounds, and board preparation. * Expedites reference and review with a question-and-answer format, bulleted lists, mnemonics, and tips from the authors;* Features a two-color page layout, "Key Points" boxes, and lists of useful web sites to enhance your referencing power; * Includes a chapter containing the "Top 100 Secrets" in physical medicine and rehabilitation, enabling you to quickly review essential material; * Comes in a convenient pocket size for easy access to key information.